Untersuchungen der Hydratation von Collagen - Madeleine Lüscher; R. Giovanoli; P. Hirter (CHIMIA)
The amount of structurally sorbed water was determined for calf skin collagen by wide angle X-ray diffraction under defined water vapour pressures and by sorption measurements.